Pharmacogenetics of efavirenz discontinuation for reported central nervous system symptoms appears to differ by race. Issue 10 (October 2016) - Leger, Paul; Chirwa, Sanika; Turner, Megan; Richardson, Danielle M.; Baker, Paxton; Leonard, Michael; Erdem, Husamettin; Olson, Lana; Haas, David W.
Abstract : Background: Efavirenz frequently causes central nervous system (CNS) symptoms. We evaluated genetic associations with efavirenz discontinuation for CNS symptoms within 12 months of treatment initiation. Methods: Patients had initiated efavirenz-containing regimens at an HIV primary care clinic in the Southeastern United States and had at least 12 months of follow-up data. Polymorphisms in CYP2B6 and CYP2A6 defined efavirenz metabolizer categories. Genome-wide genotyping enabled adjustment for population stratification. Results: Among 563 evaluable patients, 99 (17.5%) discontinued efavirenz within 12 months, 29 (5.1%) for CNS symptoms. The hazard ratio (HR) for efavirenz discontinuation for CNS symptoms in slow versus extensive metabolizers was 4.9 [95% confidence interval (CI): 1.9–12.4; P =0.001]. This HR in Whites was 6.5 (95% CI: 2.3–18.8; P =0.001) and 2.6 in Blacks (95% CI: 0.5–14.1; P =0.27). Considering only slow metabolizers, the HR in Whites versus Blacks was 3.1 (95% CI: 0.9–11.0; P =0.081). The positive predictive value of slow metabolizer genotypes for efavirenz discontinuation was 27% in Whites and 11% in Blacks. Conclusion: Slow metabolizer genotypes were associated significantly with efavirenz discontinuation for reported CNS symptoms. This association was considerably stronger in Whites than in Blacks. Abstract : Supplemental Digital Content is available in the text.